Effect of heat treatment on fatigue life - Zulqarnain, Fuad (2012)
The main purpose of this project is to determine the effect of various heat treatment processes on fatigue life of mild steel specimen. The study of fatigue life and effect of heat treatment is very important in order to increase the hardness of the material and its life before failure. The influence of heat treatment process to the specimen has been investigated. Total eighteen specimens have been machined where six were oil quenched, six were tempered and another six remained as received. The rotational bending fatigue test was conducted on all prepared specimens at room temperature with stress ratio of -1. From the fatigue test, the results show that tempered specimens has highest fatigue life compared to other two conditions. After the fatigue test have been done, the fracture surface of failed specimens were analysed to ensure that the specimens were failed due to fatigue. Based on the analysis, the mild steel specimens failed due to fatigue with transgranular manners. It was observed that there are three distinct region on specimen’s fracture surface which are crack initiation, crack propagation and rapid fracture region.